Analisis Nilai Modulus Geser Maksimum Tanah Pasir Menggunakan Data SPT di Danau Toba - Sianipar, Aris Julianto; Wulandari, Tika Ermita (VISA: Journal of Vision and Ideas, 2025)
The Lake Toba boundary area has complex geological and geomorphological characteristics due to past volcanic activity. Along with the rapid development of infrastructure and settlements in this area, in-depth geotechnical studies are needed to support safe and sustainable planning. This study aims to evaluate the maximum shear modulus (Gₘₐₓ) of soil based on Standard Penetration Test (SPT) data with an empirical approach using the formula of Hardin & Black (1968). The study location is in Nainggolan, Samosir Regency, North Sumatra. Analysis was conducted on field data in the form of N-SPT values, soil unit weight, and calculations of effective stress and effective octahedral stress. The results show that the Gₘₐₓ value tends to increase with depth, with the highest value of 60,820.13 kN/m² at a depth of 14.45–16.45 meters, and the lowest value of 14,383.66 kN/m² at a layer of 4.45–6.45 meters, indicating a weak soil zone with high pore water content. Layers with high Gₘₐₓ values are recommended as the main supporting layer of the foundation, while layers with low values require reinforcement. This study proves that the empirical correlation approach based on SPT can be a practical and economical alternative in estimating soil dynamic parameters, and can be used to support civil engineering planning and geotechnical risk mitigation in the Lake Toba area.